Bridging the gaps in palliative care bereavement support: An international perspective - Breen, Lauren; Aoun, Samar; O'Connor, Moira; Rumbold, B. (Routledge, 2013)
A review of palliative care policies and bereavement support practices in the United States, Canada, United Kingdom, Australia, and Japan demonstrated 4 challenges: questions over providing universal versus targeted support; a lack of clear evidence driving service delivery; informal or no risk assessment; and limited or no evaluation of services. Bridging the gaps between the policy and practice of palliative care bereavement support requires acknowledging the challenges of medical and public health models, improving bereavement need assessment processes, enhancing the role of primary care providers, and extending research to provide an evidence-base for interventions.